The Relationship between Physical Activity and Sleep Quality on Primary Dysmenorrhoea Pain Levels in Adolescent Girls - Ivon Nabila Ikbar; Rekawati Susilaningrum; Aris Handayani; Tatarini Ika Pipitcahyani (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2024)
Dysmenorrhea, which is characterized by pain in the lower abdomen, is the most common complaint experienced by young women, causing discomfort and can have a negative impact on their daily activities, including their academic activities. Dysmenorrhea lasts for 8-72 hours due to the release of prostaglandins. This research aims to find out the relationship between physical activity and sleep quality on primary dysmenorrhea pain in young women, especially at SMP Hang Tuah 1 Surabaya. This type of quantitative research uses a cross-sectional approach. Data collection was carried out using the PAQ-A questionnaire, PSQI Scale and pain measurement using the Numeric Rating Scale. From a population of 85, a sample of 70 female students was obtained. The inclusion criteria for this study were female students aged 14-15 years with menstrual pain on the first – third day. The research results were analyzed using the Spearman test with a p value of 0.001, showing that there was a relationship between physical activity and sleep quality and primary dysmenorrhoea in young women at SMP Hang Tuah 1 Surabaya. It is hoped that educators and school health officials will intensify the treatment of dysmenorrhoea, especially for young women.